Pengaruh Metode Out Door Study Terhadap Minat Belajar Siswa Kelas IV SD Negeri 105337 Pantai Labu Pekan Tahun Ajaran 2022/2023 - Fitria, Meri; Herdyana, Thessa; Melinda, Leni (Tematik: Jurnal Penelitian Pendidikan Dasar, 2024)
This study investigates the effect of the outdoor study method on the learning interest of fourth-grade students at SD Negeri 105337 Pantai Labu Pekan. The outdoor study method involves taking students outside the classroom to observe real-life events, aiming to foster a closer connection with their environment. The research used an experimental design, with a sample consisting of 20 students. Data were collected through documentation and questionnaires, and the analysis was performed using SPSS. The results show that the outdoor study method has a significant positive effect on students' learning interest, with a t-value of 4.575, surpassing both the 5% significance level (2.024) and the 1% significance level (2.712). These findings demonstrate that outdoor study can be an effective tool to increase students' engagement and interest in learning.